Educação infantil e cultura visual nos documentos da Rede Municipal de Educação de Goiânia - Guimarães, Julia Moreira (2023)
This dissertation proposes a analysis of the subject formation in Early Childhood Education, specifically in the Municipal Education System of Goiânia, having as a founding reference the official documents that regulate this educational stage in the municipality and the understanding that the school environment is not a neutral ground as it is being formed by many contextual layers and plural perceptions. Through the methodological perspectives of document analysis and narrative survey, the research was interested in intersecting the guidelines contained in official documents with different voices from the Municipal Department of Education, which testimonials were collected through interviews. It was examined how these documents were constructed, passed on and received and what as well are the strategies for studies and implementation in educational units. As specific questions, it was explored the role of (audio)visual artifacts in the processes of construction of knowledge in childhood and in other pedagogical dynamics and practices that contribute to the development of children in educational routines. The narratives of the people interviewed pointed out some difficulties for the full understanding of the documents that currently conduct the daily life in educational units dedicated to Early Childhood Education, especially in relation to the time allocated to studies and collective debates on the various themes present in official documents. The interviewees indicated the need to build a broader network of efforts to favor in-depth knowledge of the documents and pointed to continuing education courses as a possibility to incorporate more diversified practices into pedagogical planning, prioritizing the construction of knowledge that favors the development of ethical and democratic values within educational environments.